PP.19.15: IMPACT OF OBESITY ON THE RELATIONSHIP BETWEEN ELEVATED BLOOD PRESSURE AND CHRONIC KIDNEY DISEASE. (June 2015) - Lim, N.; Kim, M.; Park, H.
Abstract : Objective: Controlling of blood pressure (BP) is a most important countermeasure against target organ damage in hypertension patients. The aim of this study was to assess the impact of obesity on the relationship between blood pressure control during 8-year follow-up and prevalence of chronic kidney disease (CKD) in prehypertension and hypertension. Design and method: This study included 2, 482 participants aged 40–69 with prehypertension or hypertension without type 2 diabetes mellitus (T2DM) at baseline examination of Korean Genome and Epidemiology Study. CKD was defined as glomerular filtration rate (eGFR) < 60 mL/min/1.73m 2 . Controlled BP was defined as systolic BP < 120 mmHg and diastolic BP < 80 mmHg after 8-year follow-up. Multiple logistic regression analyses were used to identify the association between BP control and CKD. Results: The prevalence of CKD after 8-year follow-up was 15.4%, and it was inversely associated with BP control (10.1% (controlled BP) vs 14.4% (uncontrolled BP), P = 0.003). However, in multiple logistic regression analysis, BP control was not associated with prevalent CKD after 8 years (Table). In subgroup of obesity, uncontrolled BP was significantly associated with prevalence of CKD (OR = 2.17, 95% confidence interval (CI), 1.06–4.43, P = 0.034) while in subgroups of overweight and normal weight, poorly controlled BP was not associated with CKD (OR = 0.55, 95% CI, 0.26–1.17 and OR = 0.53, 95% CI, 0.24–1.14, P = 0.103, respectively) (Table). Figure. No caption available. Conclusions: Our results indicated that the positive association between uncontrolled BP and CKD is accentuated with obesity. Weight loss, as well as BP control, in people with prehypertension or hypertension without T2DM is important to prevent CKD event.